Phenotypic yield-attributed traits and phytochemical composition of the flowers from Alcea species in Iran - Yasaman Mashhadi Tafreshi; Ghasem Eghlima; Samad Nejad Ebrahimi (Scientific Reports)
Abstract The genus Alcea is an herbaceous, annual and perennial plant of the Malvaceae family, which is rich in flavonoids, phenolic acids, coumarins, triterpenes, alkaloids, polysaccharides (mucilage), pectins, scopoletin, asparagine, tannins, steroids, proteins and minerals. The genus Alcea has various biological properties, including antimicrobial, anti-inflammatory, antioxidant, anti-estrogenic, enzyme inhibitory and immunomodulatory effects. In this study, agro-morphological, phytochemical and proximate composition variability among six Iranian species of the plant was studied to find adequate samples for further use in breeding and exploitation programs. For this purpose, we evaluated six species of the genus Alcea in terms of functional traits, phenolic compounds, anthocyanin content, mucilage, minerals, and proximate compositions, including A. kurdica, A. tehranica, A. koelzii, A. lavateriflora, A. rechingeri, A. xanthochlora. The highest coefficient of variation was obtained for rutin, chlorogenic acid, antioxidant activity, flower dry weight. A. rechingeri species indicated the maximum (1220 g/plant) and A. xanthochlora species revealed the minimum (200 g/plant) dry flower weight. The species A. lavateriflora (32.91%), A. tehranica (23.11%), and A. rechingeri (16.40%) had the highest mucilage content. The anthocyanin content in different species varied from 11.47 (in A. koelzii) to 30.39 (in A. tehranica) mg C3G/g DW. Maximum content of total phenol (48.42 mg GAE/g DW), total flavonoid (34.32 mg RE/g DW), and antioxidant activity, were observed in A. tehranica species. Chlorogenic acid, rutin, kaempferol, and apigenin were detected as the major phenolic compounds using high-performance liquid chromatography (HPLC). The analyzed species exhibited variations in carbohydrate (42.44 to 58.62 g/100 DW), fat (1.30 to 2.53 g/100 DW), protein (6.06 to 11.30 g/100 DW), and fiber (13.34 to 28.64 g/100 DW) contents. The extraordinary diversity in terms of the studied parameters indicates the ability of different Alcea species to be selected and used in breeding, cultivation, and production programs.